Employee Performance Gains from E-Buddy Implementation in Larangan Village: Peningkatan Kinerja Karyawan dari Implementasi E-Buddy di Desa Larangan - Sakinah, Fitria Fatimah; Choiyirah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2025)
General Background: The shift toward Electronic-Based Government Systems (SPBE) necessitates the adoption of technology in local administration to modernize management and enhance public service delivery. Specific Background: The Larangan Village Government adopted the E-Buddy application to manage official correspondence, but its actual output on employee performance requires empirical scrutiny. Knowledge Gap: While E-Office adoption is increasing, studies validating its specific effectiveness using established organizational performance indicators, particularly at the village governance level, remain limited. Aims: This research analyzes the effectiveness of the E-Buddy application in improving employee performance at the Larangan Village Government, using Gibson’s five organizational performance indicators. Results: E-Buddy demonstrates effectiveness in two key areas: Production, by increasing work productivity through technological leverage, and Efficiency, by significantly reducing managerial time and costs, although recurring technical issues persist. Employee Satisfaction is informally acknowledged but requires formal measurement. Adaptation is gradual, and long-term Organizational Development is viewed optimistically. Novelty: This study provides the first comprehensive effectiveness assessment of the E-Buddy application against the Gibson performance framework in a village context, confirming its success primarily in technical efficiency. Implications: The findings suggest prioritizing technical infrastructure upgrades and establishing formal satisfaction metrics to maximize the application's benefits and ensure sustainable organizational development. Highlights: E-Buddy implementation successfully increased administrative production and managerial efficiency. Technical problems, such as network instability, remain the primary constraint. Employee satisfaction with the application's benefits is informal and requires formal assessment. Keywords:Effectiveness, Organizational Performance, E-Buddy, Productivity, Village Government.